Yojimbo [videorecording (DVD)] - Kurosawa, Akira, 1910-1998; Mifune, Toshiro, 1920-1997; Shimura, Takashi, 1905-1982; Tōno, Eijirō, 1907-1994; Watanabe, Atsushi (Criterion collection ;, 1999)
In the year 1860, a wandering samurai-for-hire turns the war between two clans fighting for control of a small town to his own advantage. A satire on greed, violence, paranoia and human weakness. Includes theatrical trailer.